Uso de larvas de Tenebrio molitor na nutrição do jundiá - Lima, Joziane Soares de (2022)
The present study aimed to evaluate the effects of including partially defatted Tenebrio molitor larvae meal (TMd) as an alternative protein source in diets for juvenile silver catfish on hematological, metabolic, antioxidant responses, performance parameters, nutrient deposition and digestive enzyme activity. Four inclusion levels of T. molitor larvae meal in mixed diets were evaluated, as well as a control diet without the inclusion of the meal. The TMd had an increase in crude protein and mineral matter, and a reduction in fat content. Most of the essential amino acids in TMd were higher than those in fishmeal and soybean meal. Performance parameters were not affected by the treatments tested. There was an increase in fat deposition, HSI, dry matter and mineral matter content of the fish. Protease activity was higher in the group fed 30% TMd and lipase activity was higher in the animals fed 40% TMd. Trypsin activity increased with the inclusion of TMd compared to the control diet. The chymotrypsin activity was not influenced. After statistical analysis it was possible to observe that the inclusion of TMd reduced all hematological parameters except the MCV. The concentration of serum amino acids increased significantly, while that of serum glucose and triglycerides decreased. Ammonia and lactate concentration and transaminase activity were significant. The levels of amino acids and glycogen in liver and muscle tissue increased. Protein was reduced in plasma, liver and muscle. The activities of antioxidant enzymes increased and free radical production decreased in fish tissues. It is concluded that TMd can be included up to 40% of the diet in the fry without affecting their performance and that for the maintenance of the blood parameters, better activity of antioxidant enzymes and reduction of free radical production TMd should be included up to 30% of the diet in juvenile silver catfish.